1968
DOI: 10.1007/bf02890712
|View full text |Cite
|
Sign up to set email alerts
|

The action of various lime soap dispersants

Abstract: The course of the lime soap-dispersing action of various surfactants has been examined by use of a titrimetric method. Two types of dispersants can be distinguished. With the addition of a surfactant of the first type, the concentration of the dispersed fatty acid increases gradually. If a surfactant of the second type is used, a definite increase of the fatty acid concentration first occurs after the addition of considerable amounts of the dispersant.Ethylene oxide adducts and sodium triethylene glycol monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Lime soap dispersing agents, as cited in the literature, include sulfated ethoxylated fatty alcohols [1], N-alkyl-N,N-dimethylamine oxide [2], nonionics derived from tallow alcohols [3], fatty amides [4], a-sulfoalkanol amide [5], sulfated alkanol fatty amides [6], as well as polymers derived from maleic acid [7]. More recently, Shukla et al [8] have reported that anionic gemini surfactants with two sulfate or sulfonate head groups have much better lime soap dispersing ability than that of single chain surfactants that have only one sulfate or sulfonate head group.…”
Section: Introductionmentioning
confidence: 99%
“…Lime soap dispersing agents, as cited in the literature, include sulfated ethoxylated fatty alcohols [1], N-alkyl-N,N-dimethylamine oxide [2], nonionics derived from tallow alcohols [3], fatty amides [4], a-sulfoalkanol amide [5], sulfated alkanol fatty amides [6], as well as polymers derived from maleic acid [7]. More recently, Shukla et al [8] have reported that anionic gemini surfactants with two sulfate or sulfonate head groups have much better lime soap dispersing ability than that of single chain surfactants that have only one sulfate or sulfonate head group.…”
Section: Introductionmentioning
confidence: 99%